MINAT BERWISATA KAUM MILENIAL DI ERA NEW NORMAL - Yusuf, Ramayani; Veranita, Mira (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
Since the Covid-19 pandemic has spread, the millennial generation's desire for tourism has had stuck. The government enforces many restrictions on social activities to prevent the spread of the Covid-19 virus. In fact, according to several studies, before this pandemic hit, millennials traveled at least once a year. Tourism is the most vulnerable sector to crises and disasters, including the health crisis we are going through. Even though these millennials are a group that is reliable enough to enliven the world of traveling, tourist visits, and supporting the development of tourism in Indonesia. Their closeness to the world with the development of digital technology, online business, and social media helps information dissemination about tourism, not only national tourism, but also international. The research method used by the researcher is a descriptive quantitative research method with a survey method using a questionnaire as a data collection tool. Data collection through questionnaires was carried out from May 11 to June 28, 2021, with a sample of 312 questionnaires. The analysis shows that the local destination that most attracts millennials today is Pangandaran Beach. Pangandaran Regional Government especially the Department of Tourism, must have started preparing to welcome tourist visits, particularly Millennials. Pangandaran tourism must prepare tourist objects that are more Instagram-able, more attractive facilities with human resources who are ready to help and serve tourists with good service quality but also continue to protect against the threat of transmission of the Covid-19 virus.